2022
DOI: 10.3390/buildings12060708
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Energy Consumption in the Workplace via IoT-Allowed Behavioural Change Interventions

Abstract: The arrival of the Internet of Things (IoT) paradigm has opened the door to a variety of services for building users. Considering the long-lasting issue of high energy use by buildings and low-energy literacy, it is tempting to use this new technology for increasing the literacy of users. This paper shows the results of a study performed in two pilot buildings with real users that have interacted with a series of energy educational interventions that encourage them in a timed and personalised way to reduce the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…We show that these savings range from 2 to 17%. While our framework differs from other research projects with similar objective in terms of setup and parameters (source of readings, input, type of analysis, and form of recommendation, dataset) making direct comparisons difficult, we should note that our findings are in accordance with other recent studies, such as Ramallo-González et al ( 2022 ) that measured how much energy can be saved if users follow prompts or recommendations for energy preservation, or Sardianos et al ( 2020 ) that reported savings from the application of their recommender system on a office building setup.…”
Section: Experimental Evaluationsupporting
confidence: 87%
See 1 more Smart Citation
“…We show that these savings range from 2 to 17%. While our framework differs from other research projects with similar objective in terms of setup and parameters (source of readings, input, type of analysis, and form of recommendation, dataset) making direct comparisons difficult, we should note that our findings are in accordance with other recent studies, such as Ramallo-González et al ( 2022 ) that measured how much energy can be saved if users follow prompts or recommendations for energy preservation, or Sardianos et al ( 2020 ) that reported savings from the application of their recommender system on a office building setup.…”
Section: Experimental Evaluationsupporting
confidence: 87%
“…A similar framework is proposed in the BENEFFICE project (Garbi et al, 2019 ) where the authors propose to leverage IoT devices to capture appliance usage patterns and recommendations, incentives and challenges to gradually shape a better energy consumer profile. Most recently, the ENTROPY project (Ramallo-González et al, 2022 ) presented a series of educational interventions that promote energy saving in a timed and personalized manner. Going one step beyond, the EM3 project (Alsalemi et al, 2019 ) builds on the habitual behavioral change and combines context-aware recommender systems and IoT in order to maximize the probability of recommendation acceptance and thus the impact of the behavioral change policy.…”
Section: Related Workmentioning
confidence: 99%
“… Selecting a subset of the features that are most valuable to develop energy forecasts and evaluate their quality 13 , 14 . Sending personalised recommendations to HVAC users use with the goal of reducing energy consumption 15 . Forecasting indoor temperature per room 16 .…”
Section: Background and Summarymentioning
confidence: 99%
“…Sending personalised recommendations to HVAC users use with the goal of reducing energy consumption 15 .…”
Section: Background and Summarymentioning
confidence: 99%
“…In a smart city, the existing waste management system is transformed into a smart system via the IoT concept. Several studies have attempted to develop an intelligent system for real-time, low-cost waste collection [ 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ]. The following literature review focuses on current research using IoT concepts to implement intelligent solid waste management systems in Mecca.…”
Section: Introductionmentioning
confidence: 99%